The Development of Smart Campus System in Indonesia - Hardi, Richki; Kamalrudin, Massila; Hashim, Ummi Rabah; Yana Hendriana; Gunawan; sumardi; Yustian; Sigit Sigalayan; Jack Febrian Rusdi; Agus Sasmito; Apri Junaidi; Anastasia Lidya Maukar (Universitas Mulia, 2019)
Dependence on technology is complicated to avoid and very difficult to separate in the digital era. It impacts the education system, especially in Indonesian higher education. Higher education institutions in Indonesia have begun to implement information and communication technology-based systems within the campus environment. Encouraged from all academic communities in higher education who expect comfort so that the importance of the role of technology. Smart Campus comes as a result of a system that uses technology and the internet as an intermediary. Smart Campus is expected to be a campus that can educate students with IT-managed methods. The smart campus is a campus that combines, combines, combines, and implements teaching and learning processes using information technology. So that all systems that support the teaching and learning process also use technology. The smart campus system can be implemented starting from the new student admission system, campus academic system, online examination system, library information system, and tuition payment system. With the smart campus, the system will reduce errors in doing work. Of course, it will also reduce the costs to be incurred by the campus.